2021
DOI: 10.1111/jvp.13035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Escherichia coli endotoxemia on danofloxacin pharmacokinetics in broilers following single oral administration

Abstract: As a fluoroquinolone antimicrobial agent, danofloxacin is mainly used to treat avian bacterial and mycoplasma infections. The pharmacokinetic characteristics of danofloxacin are usually explored in healthy animals, while those in endotoxemic broilers are still rare. This study aimed to investigate the pharmacokinetics of danofloxacin in endotoxemic broilers induced by Escherichia coli (E. coli) lipopolysaccharide (LPS) after single oral administration. Ten healthy 5‐week‐old Arbor Acres (AA) broilers with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Danofloxacin is a fluoroquinolone antibacterial developed exclusively for veterinary medicine in the 1990's ( 3 , 4 ), and it acts by inhibiting bacterial DNA-gyrase. Because of its broad antimicrobial spectrum, danofloxacin has been licensed in bovine, ovine, caprine, and poultry species ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Danofloxacin is a fluoroquinolone antibacterial developed exclusively for veterinary medicine in the 1990's ( 3 , 4 ), and it acts by inhibiting bacterial DNA-gyrase. Because of its broad antimicrobial spectrum, danofloxacin has been licensed in bovine, ovine, caprine, and poultry species ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…When normalized by the BW, the current oral C max had a value of 0.21, which was consistent with those calculated in turkeys and geese (0.195 and 0.192, respectively; Haritova et al, 2006; Sartini, Łebkowska‐Wieruszewska, Lisowski, Poapolathep, & Giorgi, 2021); however, higher than those in Japanese quail (0.078; Dimitrova et al, 2014), pheasant (0.054; Dimitrova et al, 2014), guinea fowl (0.051; Dimitrova et al, 2014), and ducks (0.162; Goudah & Mouneir, 2009). However, the previously reported C max values in broilers after oral administration at the same dosage ranged from 0.17 to 0.53 μg/ml (Knoll et al, 1999; Wang, Huang, et al, 2022; Wang, Yang, Song, Shao, Bai, et al, 2022; Wang, Yang, Song, Shao, Zhang, et al, 2022; Zeng et al, 2011), and were all lower than the current result (1.05 ± 0.20 μg/ml). A previous study observed gender‐related differences in the pharmacokinetics of sulfonamides, penicillins, and aminoglycosides (but not fluoroquinolones) in poultry (Lashev et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…A previously validated chromatographic analysis method was used to detect danofloxacin concentrations in plasma (Wang, Yang, Song, Shao, Zhang, et al, 2022) with slight modifications. Briefly, a volume ofplasma(200 μl) was mixed with two volumes of acetonitrile, then vortexed completely and centrifuged for 10 min at 10,000 g. All supernatant was collected in a clean tube, and the extraction process was repeated.…”
Section: Determination Of Danofloxacin In Plasmamentioning
confidence: 99%
“…The automatic biochemical analyzer AU5400 (Beckman Coulter Commercial Enterprise, Shanghai, China) was used to determine the levels of serum biochemical factors, including alanine transaminase (ALT), aspartate aminotransferase (AST), total protein (TP), albumin (ALB), globulin (GLO), Urea-N, creatinine (CRT), glucose (GLU), calcium, phosphorus, triglyceride (TRIG), cholesterol (CHOL), high-density lipoprotein (HDL), lowdensity lipoprotein (LDL), creatine kinase (CK), lactate dehydrogenase (LDH), glutamyltransferase (GT), and alkaline phosphatase (ALP). Based on our previous studies (16,17), the commercial enzyme-linked immunosorbent assay (ELISA) kits (Nanjing Jiancheng Bioengineering Institute, Jiangsu, China) were used to determine immunoglobulins, interleukins, and interferons levels, including IgA, IgG, IgE, IgM, IL-1, IL-6, IFN-α, IFN-β, and IFN-γ.…”
Section: Serum Biochemical Factors and Immune Factorsmentioning
confidence: 99%